2001
DOI: 10.1016/s0092-8674(01)00209-4
|View full text |Cite
|
Sign up to set email alerts
|

A Human BRCA2 Complex Containing a Structural DNA Binding Component Influences Cell Cycle Progression

Abstract: Germline mutations of the human BRCA2 gene confer susceptibility to breast cancer. Although the function of the BRCA2 protein remains to be determined, murine cells homozygous for BRCA2 inactivation display chromosomal aberrations. We have isolated a 2 MDa BRCA2-containing complex and identified a structural DNA binding component, designated as BRCA2-Associated Factor 35 (BRAF35). BRAF35 contains a nonspecific DNA binding HMG domain and a kinesin-like coiled coil domain. Similar to BRCA2, BRAF35 mRNA expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(99 citation statements)
references
References 36 publications
3
92
0
3
Order By: Relevance
“…Interestingly, BRCA2 has been linked to a G 2 /M checkpoint. 66 In these studies, microinjection of BRCA2 antibodies leads to a delay in G 2 /M progression, revealing a potential role for BRCA2 in the timing of mitosis entry. 66 More recently, Brca2 defective Chinese hamster ovary cells have been shown to undergo inappropriate "radioresistant" DNA synthesis suggesting a defect in intra-S phase checkpoints in these cells.…”
Section: Hereditary Breast Cancer and Dna Double Stranded Break Repairmentioning
confidence: 88%
“…Interestingly, BRCA2 has been linked to a G 2 /M checkpoint. 66 In these studies, microinjection of BRCA2 antibodies leads to a delay in G 2 /M progression, revealing a potential role for BRCA2 in the timing of mitosis entry. 66 More recently, Brca2 defective Chinese hamster ovary cells have been shown to undergo inappropriate "radioresistant" DNA synthesis suggesting a defect in intra-S phase checkpoints in these cells.…”
Section: Hereditary Breast Cancer and Dna Double Stranded Break Repairmentioning
confidence: 88%
“…The role of the HMG domain of Braf35 is less clear. Braf35 HMG domain binds structured DNA, such as four-way junction DNA, without sequence specificity (10). The Shiekhattar group reported that a point mutation in the HMG domain of Braf35 abrogates binding of this protein to its target genes, suggesting that the DNA-binding activity of Braf35 is important for its function (7).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to LSD1 and CoREST, the LSD1-CoREST complex also contains HDAC1-2, BHC80, and BRAF35 (also called HMG20B) (6)(7)(8)(9). BRAF35 contains a high-mobility group (HMG) domain and a coiled-coil domain, but its function within the complex is not well-understood (7,10). Several functions of the LSD1-CoREST complex in differentiation and development have been reported (2).…”
mentioning
confidence: 99%
“…BRCA2 has also been found to associate with known mitotic checkpoint proteins, such as hBUBR1 (Futamura et al, 1531), and with new proteins, such as BRAF35, in close association with phosphorylated histone H3 (Marmorstein et al, 2001). The S phase checkpoint was also found to be defective in a Chinese hamster ovary cell line mutant, recently found to be defective in BRCA2 (Kraakman-van der Zwet et al, 2002).…”
Section: Cell Cycle Checkpointsmentioning
confidence: 99%